Chemistry of Mesoporous Organosilica in Nanotechnology: Molecularly Organic–Inorganic Hybridization into Frameworks. Issue 17 (3rd March 2016) - Chen, Yu; Shi, Jianlin
Abstract : Organic–inorganic hybrid materials aiming to combine the individual advantages of organic and inorganic components while overcoming their intrinsic drawbacks have shown great potential for future applications in broad fields. In particular, the integration of functional organic fragments into the framework of mesoporous silica to fabricate mesoporous organosilica materials has attracted great attention in the scientific community for decades. The development of such mesoporous organosilica materials has shifted from bulk materials to nanosized mesoporous organosilica nanoparticles (designated as MONs, in comparison with traditional mesoporous silica nanoparticles (MSNs)) and corresponding applications in nanoscience and nanotechnology. In this comprehensive review, the state‐of‐art progress of this important hybrid nanomaterial family is summarized, focusing on the structure/composition–performance relationship of MONs of well‐defined morphology, nanostructure, and nanoparticulate dimension. The synthetic strategies and the corresponding mechanisms for the design and construction of MONs with varied morphologies, compositions, nanostructures, and functionalities are overviewed initially. Then, the following part specifically concentrates on their broad spectrum of applications in nanotechnology, mainly in nanomedicine, nanocatalysis, and nanofabrication. Finally, some critical issues, presenting challenges and the future development of MONs regarding the rational synthesis and applications in nanotechnology are summarized and discussed. It is highly expected that such a unique molecularly organic–inorganic nanohybrid family will find practical applications in nanotechnology, and promote the advances of this discipline regarding hybrid chemistry and materials. Abstract : Organic–inorganic hybrid materials combine the advantages of both organic and inorganic components while overcoming their intrinsic drawbacks, showing extensive prospective applications across broad fields. A comprehensive overview is presented of the research progress regarding the design, synthesis and structure/composition control of molecularly organic–inorganic hybrid mesoporous organosilica nanoparticles (MONs), along with their extensive applications in nanotechnology, mainly in nanomedicine, nanocatalysis and nanofabrication.